Secondary Effects of the Rupture and Reconstruction of the Interosseous Talocalcaneal Ligament on the Peritalar Joints - Liu, Chen (Med Sci Monit, 2021)
BACKGROUND: The interosseous talocalcaneal ligament (ITCL) is the main soft-tissue contributor to subtalar joint stability. The role of ITCL reconstruction in retaining this stability is minimally reported. Therefore, we conducted this study to investigate the effects of rupture and reconstruction of the ITCL on the subtalar and peritalar joints. MATERIAL/METHODS: This experimental study randomly divided 72 rabbits into 3 equal groups of 24 rabbits each. Group I underwent reconstruction surgery, group II underwent resection, and group III was the control group. The cartilages between the talocrural and calcaneocrural joints, and between the subtalar and talonavicular joints on both sides were assessed by gross observation, ink staining, histology, and immunohistochemistry at weeks 4, 8, 16, and 32, postoperatively. RESULTS: In group II, the quantitative ink staining analysis revealed degeneration of the articular cartilages on the talonavicular joint (T=2.070, P=0.038) and the posterior subtalar joint (T=2.121, P=0.034) compared with the 2 sides of the same rabbit at 4 and 8 postoperative weeks. Comparing the operated sides of all the groups showed the posterior subtalar joints (Hc=9.563, P=0.008) and talonavicular joints (Hc=9.714, P=0.008) had an obvious difference at postoperative week 4; and in the calcaneocrural joints (Hc=6.750, P=0.034), it was noticed at postoperative week 8. Histology and immunohistochemistry findings confirm these observations. CONCLUSIONS: An ITCL resection can lead to the progressive degeneration of the talonavicular and posterior subtalar joints, while an ITCL reconstruction can be beneficial in restoring the stability of these joints, preventing or postponing their degeneration, and protecting the articular cartilages.